A theory of maximalist luxury. Issue 2 (15th November 2021) - Liu, Zhenqi (Jessie); Yildirim, Pinar; Zhang, Z. John
Abstract: The availability of high‐quality, low‐price counterfeits in many luxury markets threatens the role of luxury goods as a status symbol. If those counterfeits look and feel the same as the authentic counterparts, as many professional authenticators observe, and they are available at a fraction of the price of authentic goods, why would self‐interested consumers purchase authentic luxury goods? Then, the future of luxury goods is called into question. In this paper, we propose that the presence of high‐quality, low‐price counterfeits can, surprisingly, motivate the wealthy consumers to pursue what we term as the "maximalist luxury" strategy. In the presence of these counterfeits, the wealthy can resort to signaling their status by purchasing the maximum number of luxury goods available and put their copious consumption on display, while in the absence of such counterfeits, the wealthy consumers only need to purchase the minimum number of luxury goods to stand out. This new signaling mechanism then highlights the importance of product line decisions by a luxury brand in combating counterfeits and provides a number of managerial insights about how to maintain the role of luxury goods as a status symbol through pricing, adjusting the product line, and limiting its products' functionality.